Legal Politics and the Dilemma of Legal Certainty and Justice: A Normative Analysis in the Indonesian Legal System - Marzuki Irham; Muh. Ramli (Journal AGENCY, 2026)
This study examines the role of legal politics in ensuring legal certainty and achieving substantive justice within the Indonesian legal system. Although legal politics serves as a fundamental guideline in the formulation and enforcement of laws, tensions frequently arise between the demands of legal certainty and the pursuit of justice due to political influence in the legislative process. This study aims to analyze how legal politics shapes law-making and to identify the challenges in balancing these two legal objectives. This research employs a normative juridical method, using statutory, conceptual, and theoretical approaches to analyze legal norms, doctrines, and relevant scholarly works. The analysis focuses on the interaction between political configurations, institutional integrity, and the resulting legal framework. The findings reveal that legal politics plays a strategic role in determining the direction, substance, and priorities of legislation, thereby influencing the realization of legal certainty and justice. However, the dominance of political interests, regulatory disharmony, and weak law enforcement often undermine these objectives. The study also finds that an overemphasis on formal certainty may lead to substantive injustice, highlighting the need for a balanced approach. This study contributes to the discourse by emphasizing the importance of justice-oriented legal politics that integrates formal certainty with substantive fairness. It recommends strengthening institutional integrity, enhancing public participation, and ensuring consistency in legal policy to achieve a more equitable and predictable legal system.